1994
DOI: 10.1002/cne.903400308
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural evidence for intra‐ and extranuclear projections of GABAergic neurons of the suprachiasmatic nucleus

Abstract: GABAergic projections of the suprachiasmatic nucleus (SCN) were demonstrated in a double-labelling ultrastructural study which visualised the efferents of the SCN by PHA-L tracing, diaminobenzidine (DAB) immunocytochemistry, and GABA with immunogold postembedding staining. The results show a strong contralateral projection of the SCN that is partly GABA-containing. In addition, ipsilateral SCN projections to the dorsomedial hypothalamus and periventricular part of the paraventricular nucleus and sub-paraventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
93
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 30 publications
5
93
1
1
Order By: Relevance
“…This is important as GABA is the main neurochemical used to mediate synaptic transmission within the SCN (Moore and Speh 1993;Buijs et al 1994). Agonists of GABAa receptors phase advance the in vitro SCN of hamsters during the day (Tominaga et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important as GABA is the main neurochemical used to mediate synaptic transmission within the SCN (Moore and Speh 1993;Buijs et al 1994). Agonists of GABAa receptors phase advance the in vitro SCN of hamsters during the day (Tominaga et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The SCN receive extensive GABAergic innervation (Buijs et al 1994) and nearly all of the neurones in the SCN are GABA-producing (Moore and Speh 1993). Many phase shifting stimuli are thought to involve GABA in their actions on the circadian clock, and it is likely that it plays a significant role in regulating entrainment.…”
mentioning
confidence: 99%
“…2 B). The nature of the nuclear labelling in GABAergic neurons in the SCN is unclear, both in terms of the identity of the immunoreactive epitopes and the functional implications, as noted also by Buijs et al (1994Buijs et al ( , 1995. Nevertheless, similar marking of GABAergic nuclei in other parts of the brain is regarded as not understood rather than nonspecific (P. Somogyi, personal communication).…”
Section: Gabaergic Somatamentioning
confidence: 99%
“…A number of immunocytochemical studies have shown that GABA appears to be the most ubiquitous neurotransmitter in the SCN (Okamura et al 1989 ;Castel et al 1990 a, b ;Decavel & Van den Pol, 1990 ;Moore & Speh, 1993 ;Buijs et al 1994Buijs et al , 1995Belenky et al 1996). However, less attention has been paid to the heterogeneity of the GABA-containing elements in the SCN, as a possible basis for the multiple roles played by this neurotransmitter in circadian regulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation